Planning and Forestry Development - Bhatia, H. M. (Indian Forester, 1990)
The forestry planning has undergone a remarkable change since the inception of 5 year plans. Critical analysis of the objectives of various five year plans shows that there has been change in every plan keeping in view of the various national/local requirements and ecological/ environmental considerations. The invest ment has also gradaully risen but still remains to be meagre in view of the deforestation taking place and need for maintaining ecological balance for sustainable development. Forestry has been given less priority as compared to other sectors such as energy, irrigation, industry etc. which are getting major share of plan investments Some important programmes/schemes should be idenlified for 8th plan and given high priority. The area like protection and regeneration of natural forests; raising, harvesting, processing and marketing of Minor Forest Produces, tribal welfare, wildlife conservation etc. should be given new thrusts.